2020
DOI: 10.1371/journal.pone.0230287
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different species of Zanthoxyli Pericarpium based on convolution neural network

Abstract: Zanthoxyli Pericarpium (ZP) are the dried ripe peel of Zanthoxylum schinifolium Sieb. et Zucc (ZC) or Zanthoxylum bungeanum Maxim (ZB). It has wide range of uses both medicine and food, and favorable market value. The diverse specifications of components of ZP is exceptional, and the common aims of adulteration for economic profit is conducted. In this work, a novel method for the identification different species of ZP is proposed using convolutional neural networks (CNNs). The data used for the experiment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The Framework of AlexNet model was demonstrated in Figure 8. Previously, CNNs have been used successfully to identify different cells or species [6,8,14,[18][19]. This study also con rmed the e ciency of CNNs in identifying y species.…”
Section: Resultssupporting
confidence: 72%
“…The Framework of AlexNet model was demonstrated in Figure 8. Previously, CNNs have been used successfully to identify different cells or species [6,8,14,[18][19]. This study also con rmed the e ciency of CNNs in identifying y species.…”
Section: Resultssupporting
confidence: 72%
“…Previously, CNNs have been used successfully to identify different cells or species 11 18 , 26 , 27 . This study also confirmed the efficiency of CNNs in identifying fly species.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, CNNS have been successfully used in a wide range of scientific discipline including Entomology 11 – 19 , 26 , 27 . This study demonstrated that all state-of-the-art CNNs used in this study including ResNet-101, Densenet161, Vgg19_bn, and AlexNet provided high efficiency in the computer vision aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Z. schinifolium is distributed in more than 20 provinces in China including Sichuan. Sichuan- Z. schinifolium are also a popular food additive and widely used in cooking with the history of more than 1000 years for both medicinal and economic values [ 109 ].…”
Section: Food Functionsmentioning
confidence: 99%